Stereoelectronic Effects: Perlin Effects in Thiane‐Derived Compounds. Issue 19 (7th April 2020) - Jung, Sebastian T.; Basche, Luis; Reinsperger, Tony; Luy, Burkhard; Podlech, Joachim
Abstract : Stereoelectronic effects in thianes and thiane‐derived sulfoxides, sulfones, sulfilimines, and sulfoximines were investigated by measuring 1 J C, H coupling constants and by identification of normal and reversed Perlin effects, i.e., of differences in the coupling constants for equatorial and axial C–H bonds in the methylene groups of six‐membered rings. The Perlin effects were correlated with results from natural bond orbital (NBO) analyses. NMR experiments were performed with conformationally restricted dimethyl‐ or tert ‐butyl‐substituted derivatives, while the parent compounds were used for calculations. It turned out that the coupling constants are not only strongly influenced by stereoelectronic interactions with antiperiplanar C–H, C–C, C–O, and C–N bonds, but by the s character of the respective C–H bonds' carbon orbital as well. Abstract : Equatorial and axial hydrogens in methylene groups of six‐membered rings show differing coupling constants (Perlin effects) dependent on the adjacent functional groups. The coupling constants are influenced by stereoelectronic effects and by the hybridizations of the carbons.